FAMILY, NEIGHBORHOOD AND COLLEGE SPIRITUAL - EDUCATIONAL COOPERATION STATUS OF SOCIAL PEDAGOGICAL RESOURCES (Archive of Conferences, 2020)
The article provides technologies and recommendations for improving the social partnership of the family, community and educational institution in educating young people in Uzbekistan.